2015
DOI: 10.1128/jvi.03711-14
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Tomato Bushy Stunt Virus RNA-Dependent RNA Polymerase by Cellular Heat Shock Protein 70 Is Enhanced by Phospholipids In Vitro

Abstract: Similar to other positive-strand RNA viruses, tombusviruses are replicated by the membrane-bound viral replicase complex (VRC). The VRC consists of the p92 virus-coded RNA-dependent RNA polymerase (RdRp), the viral p33 RNA chaperone, and several co-opted host proteins. In order to become a functional RdRp after its translation, the p92 replication protein should be incorporated into the VRC, followed by its activation. We have previously shown in a cell-free yeast extract-based assay that the activation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 72 publications
0
33
0
Order By: Relevance
“…Tombusvirus replication greatly depends on phospholipid levels, especially on phosphatidylethanolamine (PE), which is highly enriched within the replication compartment [ 43 ]. PE is required for TBSV replication in an artificial vesicle- (liposome)-based in vitro assay [ 43 ] and it enhances the activation of the p92 RdRp in vitro [ 62 ]. Moreover, the PE level is increased during TBSV replication in yeast and plant cells and high PE level in yeast via modulation of phospholipid biogenesis genes also leads to enhanced TBSV replication [ 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Tombusvirus replication greatly depends on phospholipid levels, especially on phosphatidylethanolamine (PE), which is highly enriched within the replication compartment [ 43 ]. PE is required for TBSV replication in an artificial vesicle- (liposome)-based in vitro assay [ 43 ] and it enhances the activation of the p92 RdRp in vitro [ 62 ]. Moreover, the PE level is increased during TBSV replication in yeast and plant cells and high PE level in yeast via modulation of phospholipid biogenesis genes also leads to enhanced TBSV replication [ 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…The elevated PC has been proposed to serve as a building block for the formations of the viral replication factory [68,69]. Recently, it has been shown that PE and PC stimulate TBSV RdRP activity in vitro [70]. RCNMV p27 showed affinity, not only for PA but also for other phospholipids such as PI4P in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…First, by being on a membrane, viral protein movement becomes restricted to a two dimensional plane, thus potentially saving time for proteins to find each other and form a complex, a significant advantage to getting replication going in the early stages of infection when viral proteins are a minority in the host cell [5]. Secondly, docking on membrane lipids can modulate enzymatic activity [6,7,8]. Lastly the architecture of the membranes can facilitate replication by generating pockets in which to concentrate viral machinery and protect from host innate immune defenses [2,9-11].…”
Section: Building Viral Replication Organellesmentioning
confidence: 99%
“…Many plant as well as some insect-vectored animal (+) ssRNA viruses appear to be dependent on phosphatidylethanolamine (PE) enriched membranes for replication and depletion of PE significantly inhibits viral RNA synthesis [6,8, 46,47]. The plant viruses TBSV, Cymbidium ring spot virus and Cucumber Necrosis Tombus virus all generate their PE enriched replication organelles from primarily peroxisome membranes while Carnation Ring Spot virus and the insect-vectored animal viruses Nodamura and flock house exploit the mitochondrial outer membrane for this purpose [6, 47].…”
Section: Other Panviral Lipids Regulating Viral Replicationmentioning
confidence: 99%
See 1 more Smart Citation